2017
DOI: 10.5888/pcd14.160034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mindfulness Practices in the US Workforce: National Health Interview Survey

Abstract: IntroductionMindfulness-based practices can improve workers’ health and reduce employers’ costs by ameliorating the negative effect of stress on workers’ health. We examined the prevalence of engagement in 4 mindfulness-based practices in the US workforce.MethodsWe used 2002, 2007, and 2012 National Health Interview Survey (NHIS) data for adults (aged ≥18 y, n = 85,004) to examine 12-month engagement in meditation, yoga, tai chi, and qigong among different groups of workers.ResultsReported yoga practice preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…Using nationally representative data, Kachan et al. () showed that among US workers, meditation rates increased significantly from 8.0% in 2002 to 9.9% in 2007 and reported that yoga practice prevalence nearly doubled from 6.0% in 2002 to 11.0% in 2012.…”
Section: Factors Promoting the Dissemination Of Mbismentioning
confidence: 99%
See 1 more Smart Citation
“…Using nationally representative data, Kachan et al. () showed that among US workers, meditation rates increased significantly from 8.0% in 2002 to 9.9% in 2007 and reported that yoga practice prevalence nearly doubled from 6.0% in 2002 to 11.0% in 2012.…”
Section: Factors Promoting the Dissemination Of Mbismentioning
confidence: 99%
“…People with an affinity to Asian spirituality might be especially motivated to integrate mindfulness into their practice if they work in the health-care system or might favor MBIs in contrast to other treatment approaches if they are potential clients or patients. As interest in Buddhism and meditation practice is quite prevalent in modern western societies (Kachan et al, 2017), the dissemination of MBIs might have been supported by this segment of the society with an affinity to "Asian spirituality" because MBIs offer the possibility to match personal values and beliefs with a professional practice of proven effectiveness. 3.…”
Section: Spirituality In Mbismentioning
confidence: 99%
“…In this period of internationally and historically high rates of chronic disease, especially stress-related disease, we also see increasing (or, perhaps, re-emerging) interest in contemplative practices such as meditation and yoga. The field of health promotion is ripe to integrate contemplative practice into community-based program design as society responds to mounting stressors and dissonance, and grows toward what nourishes it, including secular opportunities for contemplative practice and self-care (21). Campus designers and planners can respond to these forces by facilitating an ecology of designated or repurposed contemplative space, recognizing the value of these places to help individuals develop contemplative skills for effective stress management and enhanced capacity to constructively engage with the complexity of the modern life and world issues that increasingly impact all of us each day.…”
Section: Resultsmentioning
confidence: 99%
“…Arthur Kleinman, a psychiatrist and anthropologist, describes shared presence as "an interpersonal process that mobilizes vitality from both clinician and patient, and from family caregiver and recipient of care" (20). Even outside of healthcare, there appears to be increasing interest in contemplative practices in the workplace, most notably yoga and meditation (21).…”
Section: Campus Environments For Contemplative Practicesmentioning
confidence: 99%
“…For example, analyses of data from the 2002, 2007, and 2012 National Health Interview Survey Alternative Medicine Supplement (Olano et al, 2014) indicated significant lower odds of engagement for Black and Hispanic respondents (vs. White respondents), and for respondents with a high school education or less (vs. respondents who attended at least some college). A second analysis of the same data set indicated that white-collar workers were far more likely to engage in mindfulness and related practices than other worker groups (Kachan et al, 2017). Additional research is needed to demonstrate the transportability and acceptability of mindfulness practices to diverse participant groups.…”
Section: Introductionmentioning
confidence: 98%